Analisis Determinan Masalah Stunting di Kabupaten Banjar - Lestari, Pratiwi Puji; Rahmah, Afiatun; Mutmainah, Shofura Ghoida (INVOLUSI: Jurnal Ilmu Kebidanan, 2025)
This study analyzes the determinants of stunting among toddlers in Banjar Regency. Using a cross-sectional analytical approach, data were collected from 115 respondents through surveys and secondary sources from Lok Baintan 3 Health Center. The findings reveal that 60% of toddlers experienced stunting. Key determinants investigated include clean water access, sanitation facilities, immunization status, exposure to cigarette smoke, and health insurance coverage. Among these, cigarette smoke exposure was identified as the most significant factor, with a p-value of 0.004, indicating a strong association with stunting. This research underscores the need for multi-sectoral interventions focusing on smoking cessation and improving nutritional support to address stunting comprehensively. Recommendations are provided for further research and policy implementation to reduce stunting prevalence